Outer-Membrane Protease (ompt) Based E.coli Sensing With Anionic Polythiophene and Unlabeled Peptide Substrate - Sinsinbar, Gaurav; Yıldız, Ümit Hakan; Gudlur, Sushanth; Wood, Sarah E.; Ammanath, Gopal; Yıldız, Ümit Hakan; Alagappan, Palaniappan; Liedberg, Bo (John Wiley and Sons Inc., 2020)
E. coli and Salmonella are two of the most common bacterial pathogens involved in foodborne and waterborne related deaths. Hence, it is critical to develop rapid and sensitive detection strategies for near-outbreak applications. Reported is a simple and specific assay to detect as low as 1 CFU mL(-1)of E. coli in water within 6 hours by targeting the bacteria's surface protease activity. The assay relies on polythiophene acetic acid (PTAA) as an optical reporter and a short unlabeled peptide (LL37(FRRV)) previously optimized as a substrate for OmpT, an outer-membrane protease on E. coli. LL37(FRRV)interacts with PTAA to enhance its fluorescence while also inducing the formation of a helical PTAA-LL37(FRRV)construct, as confirmed by circular dichroism. However, in the presence of E. coli LL37(FRRV)is cleaved and can no longer affect the conformations and optical properties of PTAA. This ability to distinguish between an intact and cleaved peptide was investigated in detail using LL37(FRRV)sequence variants.
PubMed: 32618102
Keywords: enzymes; fluorescence; membrane proteins; pathogens; peptides